Organizational culture and gender inequality as contributing factors to the overload faced by professionally active women mothers - Oliveira , Náthaly Rufato; Bana , Cesar Augusto (Seven Editora, 2023)
This study aims to characterize the relationship between the organizational culture of companies and the overload factors of female workers after maternity, from a gender perspective. For this, a review of the pre-existing literature and the application of a standardized questionnaire was used as a method, which obtained 22 responses, of which 13 were from women who were within the desired range, that is, mothers and workers of private companies in the region. the metropolitan area of São Paulo, forming the analysis group. Among the results obtained, it was found that 76.9% of them had already thought about postponing motherhood to dedicate themselves to their careers, and 100% considered themselves to be, to some degree, overloaded. These and other data brought forward illustrate the challenge that most women face when experiencing motherhood and working in organizations, which often are not prepared to receive them. DOI:https://doi.org/10.56238/devopinterscie-159